Falsification of history: to the problem - Y. A. Nikiforov (MGIMO University Press, 2009)
The author analyses state of the Russian study ofWWII and shows the scientifical unfoundedness of the so-called "new approach to the history". As author underlines, historians are to work out the scientific criteria to help the reader define scientific study and false, to defend history as a science, to prevent mass-media to do the contrary.